2020
DOI: 10.1016/j.ijid.2020.06.096
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic identification of human Gemykibivirus-2 (HuGkV-2) in parenterally infected blood donors from the Brazilian Amazon

Abstract: To metagenomically analyse blood units originating from the Brazilian Amazon and positive for parenterally transmitted infections (human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), human T-lymphotropic virus (HTLV), Chagas disease or syphilis). Methods: Twenty plasma samples (35% HBV-positive, 10% HIV-positive, 10% HCV-positive, 20% positive for syphilis, 20% for Chagas disease, and 5% for HTLV) assembled in pools were analysed by metagenomic next-generation sequencing. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…MH734253). GemyCV-SL1 has been detected in various human samples [ 27 , 28 , 29 , 30 ], including sterile sites such as cerebral spinal fluid, but the clinical significance of the virus infection is not established. To date, only one case study of a patient with respiratory distress provided evidence for the virus being the causative agent of disease [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…MH734253). GemyCV-SL1 has been detected in various human samples [ 27 , 28 , 29 , 30 ], including sterile sites such as cerebral spinal fluid, but the clinical significance of the virus infection is not established. To date, only one case study of a patient with respiratory distress provided evidence for the virus being the causative agent of disease [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gemykibivirus belongs to a divergent group of single-stranded DNA viruses, and it was detected in some MSM with or without HIV-1 infection. Several studies showed its presence/enrichment in HIV-1infected people and also patients with other diseases (30)(31)(32)(33), which suggested this virus could be associated with human disease (34). Even though more evidence is still needed, the detection of gemykibivirus here raises question about its pathogenic role in human.…”
Section: Discussionmentioning
confidence: 98%
“…The swift progress of next-generation sequencing (NGS) technology coupled with metagenomics has proven adept at unveiling a spectrum of novel circular ssDNA viruses encoding the Rep protein (Circular Rep-encoding Single-Stranded DNA) or RNA viruses [9]. These advancements extend across various specimen categories, encompassing fecal samples [10], heterogeneous mixtures [11], human subjects [12][13][14], bat populations [15], turtles [16], avian species [17], insects [18,19], plants [20], parasites [21,22], and environmental matrices [23]. This technological synergy facilitates the isolation and comprehensive characterization of viral diversity within diverse ecosystems.…”
Section: Introductionmentioning
confidence: 99%